Science Friction: Streamlined Forensic Reporting, Reliability and Justice. (27th September 2018) - Edmond, Gary; Carr, Sophie; Piasecki, Emma
Abstract: Streamlined forensic reporting (SFR), introduced as part of the United Kingdom Ministry of Justice's drive to deliver swift and sure justice, is credited with generating both time and cost efficiencies. Through the provision of radically abbreviated forensic reports at an early stage in criminal proceedings, SFR is said to avoid the cost of long form reports, facilitate agreement between the parties, secure more guilty pleas and reduce the number of defence challenges to forensic science evidence. This article questions these claims and the value of SFR as conceived. It suggests that the limited empirical evidence is mixed, and that SFR is incompatible with emerging trends and the best advice on the presentation of forensic science evidence. SFR directs little attention to the quality—that is, the validity and scientific reliability—of forensic science evidence. In overlooking quality, SFR introduces new risks of misrepresentation, misunderstanding and mistakes, and is unlikely to align with long-standing and fundamental criminal justice values (such as transparency, rationality, rectitude, equality of arms and fairness), and so is unlikely to fulfil the fundamental goal of dealing with cases justly.